Plágio, sanções sociais e marcas intertextuais - Santos, José Elderson de Souza (2020)
This research analyzes the different social sanctions that plagiarism receives in different genres, from the news about occurrences of the phenomenon in scientific articles (scientific/academic discursive domain), in songs (literary-musical domain) and in news (journalistic domain). In these genres, movements of co-presence and derivation are identified in order to propose intertextual marks of the search for disguise in plagiarism. Thus, we seek to give discursive and textual explanations to the organization of plagiarism, investigating it according to the theoretical-methodological apparatus of Textual Linguistics. Based on Christofe (1996) and Chaves (1981), socio-historical and legal issues related to the phenomenon are addressed. Ahead, there is the intersection of voices in the discourse, the notions of subject and authorship, with support in Bakhtin (2006), Amossy (2008), Foucault (2001) and Maingueneau (2010). The domains and discursive genres are treated based on Marcuschi (2008), Bakhtin (1997) and Bazerman (2005). The concept of social sanctions is based on Radcliffe-Brown (1970). Then, plagiarism is discussed within the theoretical framework of the intertextual processes studied in Textual Linguistics, from Genette (2010), Piègay-Gros (2010), Sant'Anna (2003) and the unfolding of their conceptions in approaches such as those of Cavalcante and Brito (2011) and Nobre (2014). Following the organization of social sanctions proposed by Radcliffe-Brown (1970), the variation in the sanctioning acts handed down to plagiarism was examined. In addition, it was analyzed how plagiarism is configured incorporating movements of different intertextual processes, starting from the analytical parameters studied by Nobre (2014). For analysis, three accusations of plagiarism were selected, one in each domain and gender established, in which it is possible to analyze the sanctions given to the phenomenon, organized and diffuse, and the intertextual arrangements of the plagiarism texts involved. The results show the tendency for the sanctions received for illicit appropriation to vary according to the domains and genres in which plagiarism occurs. This reality is conditioned by the fact that the texts are susceptible to previous (socio-historically constituted) dispositions of interpretation, evaluation and/or production of linguistic phenomena, to which the subjects are subjected when interacting through genres linked to specific communities. It is also verified that plagiarism incorporates intertextual movements that are linked to other intertextual processes (investigating citation, paraphrase, parody and pastiche).